1995
DOI: 10.1111/j.1432-1033.1995.561_2.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Aspergillus niger of the Starch‐Binding Domain of Glucoamylase

Abstract: Glucoamylase 1 from Aspergillus niger is an economically important enzyme in many industrial processes. It hydrolyses granular starch and comprises two distinct domains, a catalytic and a starchbinding domain (SBD). We have transformed A. niger with an expression vector for the secretion of SBD for physico-chemical studies. This was achieved by introducing into the glucoamylase gene a short sequence encoding an endoproteolytic cleavage recognition site such that free SBD was secreted at yields up to 200 mg/l. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…G1 and G2 were obtained from crude glucoamylase (Sigma) by chromatographic methods, as described [12]. SBD was expressed in A. niger with a pIGF fusion vector and purified as described [13]. Other chemicals were obtained from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…G1 and G2 were obtained from crude glucoamylase (Sigma) by chromatographic methods, as described [12]. SBD was expressed in A. niger with a pIGF fusion vector and purified as described [13]. Other chemicals were obtained from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…SBD can be isolated by proteolysis of RSDE. The Aspergillus niger SBD was cloned, expressed, and purified as a fully domain in A. niger and Saccharomyces cerevisiae [94][95][96]. It has been demonstrated that the SBD independently retains its function even if fused to a protein other than amylase.…”
Section: Adorability and Sbdmentioning
confidence: 99%
“…The complete gene sequences of genes agtA and agtB were amplified with specific primers from genomic DNA isolated from A. niger NRRL3122 (67 (41). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blotting were performed according to standard protocols.…”
Section: Methodsmentioning
confidence: 99%